Tukar Guling Tanah Wakaf dan Penarikan Kembali Harta Benda Wakaf - Syamsurizal Abas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
This paper discusses the exchange of waqf land and the withdrawal of waqf property. Waqf is a legal act of wakif to separate and/or surrender part of his property to be used forever or for a certain period of time in accordance with his interests for the purposes of worship and/or general welfare according to sharia. Waqf swap is an activity of exchanging waqf land with new land for later transfer. Basically, changes to the designation or use of waqf property other than those pledged in the waqf pledge cannot be changed. Some of the Syafi'iyyah and Malikiyah scholars are of the opinion that waqf objects that are no longer functioning, still cannot be sold, exchanged or replaced and moved. In the context of the withdrawal of waqf objects, Abu Hanifah, argues that someone who waqf his property while he is still alive has the right to cancel the waqf by withdrawing his property. For Syafi'iyah scholars, waqf is binding and therefore cannot be withdrawn or traded, pawned, and inherited by the wakif.